PENDIDIKAN AKHLAK: DASAR PEMBINAAN MORAL GENERASI BANGSA - Edyanto Edyanto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2018)
Moral education is seen as part of national education goals. Moral education is considered as the first step indirecting students to a better path. This assessment is very realistic, considering the condition of students todayis increasingly alarming. Even though they are in an educational institution, students prefer to be uneducated.Some of them are trapped in various social crimes. Starting from criminal, criminal and other crimes. Thisappalling condition is a reflection for all parties, especially education practitioners. Education practitionersconsider it important to find alternative ways to improve this educational condition. There are educationaldirections and missions that are uprooted due to the temptations of the times. Thus, moral or moral educationwhen a situation like this is considered to be the answer to this problem.Key Word: Pendidikan, Akhlak, Moral Bangsa AbstrakPendidikan akhlak dipandang sebagai bagian tujuan pendidikan nasional. Pendidikan akhlak dinilai sebagailangkah awal dalam mengarahkan anak didik ke jalan yang lebih baik. Penilaian ini sangat realistis, mengingatkondisi pelajar dewasa ini semakin memprihatinkan. Meskipun berada di dalam lingkungan lembaga pendidikan,namun anak didik lebih suka menjadi oknum yang tidak terdidik. Sebagian dari mereka terjebak dalam berbagaikejahatan sosial. Mulai dari tindak pidana, kriminal dan kejahatan lainnya. Kondisi yang memprihatinkan inimenjadi bahan renungan bagi semua pihak lebih-lebih para praktisi pendidikan. Para pemerhati praktisi pendidikanmenganggap penting dalam mencari jalan alternatif untuk membenahi kondisi pendidikan ini. Ada arah dan misipendidikan yang tercerabut akibat godaan zaman. Maka, pendidikan moral atau akhlak di saat situasi seperti inidianggap akan menjadi jawan persoalan ini.Kata Kunci: Pendidikan, Akhlak, Moral Bangsa